Metaverse Dakwah: Rekonstruksi Ruang Sakral dan Pengalaman Religius dalam Ibadah Virtual - Iim Said Sabiq (Penerbit Cahaya Kata, 2026)
The evolution of Web 3.0 technology has birthed the Metaverse, an immersive digital reality blurring the lines between the physical and the virtual. This phenomenon presents both new challenges and opportunities for dawah activities and religious practices. This study aims to analyze how sacred space is reconstructed within the Metaverse environment and how it affects the religious experience of users (avatars). Using a qualitative method with a digital phenomenology approach and literature review, this research explores the ontology of worship in cyberspace. The results indicate that the Metaverse is capable of reconstructing sacred space through symbolic manipulation and audio-visual atmosphere, yet it faces theological challenges regarding the validity of ritual worship (ibadah mahdhah) which requires physical presence (ittihad al-majlis). Psychologically, the Metaverse offers a